1988
DOI: 10.1073/pnas.85.23.9317
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of invasion plasmid antigen genes (ipaBCD) from Shigella flexneri.

Abstract: The large invasion plasmid of Shigella flexneri M90T-W was used to generate recombinant plasmids carrying the ipa4, -B, -C, and -D genes, whose products are associated with the entry of the bacteria into colonic epithelial cells. Complete DNA sequences of ipaB, -C, and -D were determined. The proteins predicted (62, 42, and 37 kDa, respectively) from the nucleotide sequences lack a signalpeptide sequence. Hydrophilic segments of the IpaB and IpaC proteins were found to overlap known epitopic domains ofthese me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
99
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 29 publications
7
99
0
Order By: Relevance
“…The YscS homolog from Y. pseudotuberculosis is also involved in the export of Yop proteins (5). A distinct feature of these export pathways is that the virulence proteins selected for export lack cleavable signal peptide sequences (2,15,38,57). Similarly, a hallmark of the flagellar export pathway is that the axial proteins, which must be transported through the pore of the growing flagellum, lack cleavable signal sequences (20,34), whereas the ring proteins have potential cleavable signal peptides at their amino termini (12,18,19,20,26,29).…”
Section: Vol 177 1995mentioning
confidence: 99%
“…The YscS homolog from Y. pseudotuberculosis is also involved in the export of Yop proteins (5). A distinct feature of these export pathways is that the virulence proteins selected for export lack cleavable signal peptide sequences (2,15,38,57). Similarly, a hallmark of the flagellar export pathway is that the axial proteins, which must be transported through the pore of the growing flagellum, lack cleavable signal sequences (20,34), whereas the ring proteins have potential cleavable signal peptides at their amino termini (12,18,19,20,26,29).…”
Section: Vol 177 1995mentioning
confidence: 99%
“…The unique SmaI site of the multiple cloning cassette of pMMB66EH and the NdeI site of the ipgC gene (Baudry et al, 1988;Venkatesan et al, 1988;Sasakawa et al, 1989) of pSEB2 were used to construct a deletion within ipgC ( Figure IA). pSEB2 was digested with SmaI and NdeI and the NdeI site was blunt ended using T4 polymerase.…”
Section: Cloning Of the Ipgc And Ipab Genes Into Plasmid Pmmb66ehmentioning
confidence: 99%
“…Both the mxi and spa genes code for the secretion apparatus to release the Ipa proteins (8)(9)(10)(11)(12). Through transposon insertion and deletion mutagenesis, it has been demonstrated that the ipaB, ipaC and ipaD genes belong to the same transcriptional unit and are essential for bacterial entry into epithelial cells via directed phagocytosis (12)(13)(14)(15). Expression of the ipaBCD genes is positively regulated by virF and invE (virB) genes on the invasion plasmid (16,17).…”
mentioning
confidence: 99%
“…Cri Locus Increasing the Expression of ipaB at Transcriptional Level The ipaBCD genes are transcribed mainly as one transcriptional unit (13,31). In order to find whether cri increases the expression of ipa genes at the transcriptional level, we performed Northern blot analysis of total RNAs prepared from E. coli K-12 MC 1061 carrying pJK1142 alone or MC 1061 carrying pJK1142 plus pQ446 (en).…”
mentioning
confidence: 99%